Hardware is the new Software - Baumann, Andrew (16th Workshop on Hot Topics in Operating Systems, 2017)
Moore's Law may be slowing, but, perhaps as a result, other measures of processor complexity are only accelerating. In recent years, Intel's architects have turned to an alphabet soup of instruction set extensions such as MPX, SGX, MPK, and CET as a way to sell CPUs through new security features. Unlike prior extensions, which mostly focused on accelerating user-mode data processing, these new features exhibit complex interactions and give system designers plenty to think about. This calls for a rethink of how we approach the instruction set. In this paper we highlight some of the challenges arising from recent security-focused extensions, and speculate about the longer-term implications.